SPIRIT KI HADJAR DEWANTARA DALAM IMPLEMENTASI KURIKULUM MERDEKA - Junaedi, I Komang (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This research aims to conduct a study related to the role of Ki Hadjar Dewantara's spirit of education in Indonesia in the implementation of the Merdeka Curriculum. Ki Hadjar Dewantara is a national hero known as the Father of Indonesian Education, he is the founder of Taman Siswa who coined the concept of the Tri Center of Education, namely informal, formal and non-formal. In addition, he also came up with a concept that became a slogan for education actors, namely